Development of oil palm empty fruit bunch tablet as corrosion inhibitor for mild steel acid corrosion - Haris, Nur Izzah Nabilah (2021)
The use of inhibitors is a prevailing corrosion control practice. However, the toxicological and environmental issues of conventional inhibitors have eloquently proliferated interest in developing safe and environmentally benign inhibitors. As considerable experimental evidence of nature-based inhibitors have been reported, their effectiveness are indisputable. Nonetheless, a breakthrough in this field is needed to go beyond the exploratory stage, seeking ways to implement the developed inhibitors in the industry. Considering the subject matter, this study aimed to develop an oil palm empty fruit bunch (OPEFB) tablet as a corrosion inhibitor for mild steel in 1 M hydrochloric acid (HCl). Two OPEFB treatments and one without treatment, that yield untreated, sodium hydroxide (NaOH) treated, and HCl treated OPEFB were used for inhibitor preparation. All inhibitors have been characterised and the results revealed that each inhibitor constitutes varying proportions of hemicellulose, cellulose, lignin, and extractives. The inhibition efficiencies of the inhibitors have been investigated using weight loss method at varying dosages from 0.1 to 0.5 g. The finding has shown that HCl treated OPEFB exhibited the highest inhibition efficiency (85.66%), followed by untreated (82.11%) and NaOH treated OPEFB (66.24%). All OPEFB inhibitors’ adsorptions on mild steed obeyed Langmuir isotherm and are categorised as mixed-type adsorption. HCl treated OPEFB was selected to be further characterised and investigated. Its chemical composition was explored and the results unveiled that the inhibitor comprises sugar, fatty acid, amino acid, carotenoid, and phytosterol compounds. The dosage and immersion time were then optimised using response surface methodology (RSM) to obtain maximum inhibition efficiency. An optimum point at 0.33 g and 120 h that yields 87.11% of efficiency was predicted and validated. Next, the inhibition kinetics was studied using electrochemical methods. The results uncovered that HCl treated OPEFB was a mixed type inhibitor that inhibits both anodic and cathodic reactions simultaneously. Afterwards, 15 HCl treated OPEFB compounds were analysed computationally. The results revealed that the sugar compounds exhibited good characteristic, while the carotenoid compound showed a superior characteristic for corrosion inhibition. All compounds were adsorbed in a flat position on the metal surface. Finally, an OPEFB tablet was formulated to extend the effective inhibition time using D-optimal mixture method. Three formulations with excellent inhibition performances were selected for tensile strength, disintegration time, and dissolution profile evaluations. The findings unveiled that T3, with OPEFB to GA to HPMC ratio of 66:0:34, portrayed the best tablet properties. The inhibition performance of T3 at extended immersion times from 120 h to 720 h was then investigated. The finding unveiled that T3 showed persistent inhibition effect up to 360 h. Overall, this study’s findings have shown that the OPEFB inhibitor tablet can inhibit mild steel acid corrosion effectively, and the tableting approach provides a promising way to implement nature-based inhibitors in the industry.